(NaRII IZ RANNIH KOMI^ESKIH OPER (B((NBARITON(B).s (NNOTYs - (NdV(B.(NrOSSINI(B.s ((NsANKT(B-(NpETERBURG(B.s (NlAN_s (NpLANETA mUZYKIs, 2022)
(NsBORNIK POSWQ]EN MUZYKE WYDA@]EGOSQ KOMPIZITORA dVOAKKINI rOSSINI (B(1792-1868).s
Keywords: (NaRIIs